Polymeric nanocomposites from renewable resources - Altuntaş, Esra. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
Objective of this study was to synthesize renewable polymeric nanocomposites by using an in-situ polymerization method and characterize them in terms of thermal and mechanical properties as well as morphology. Firstly, renewable soy bean oil based intercalant was synthesized, and it is characterized by HNMR and FTIR techniques. By using this intercalant which is quarternized derivative of acrylated epoxidized soy bean oil (AESO), modification of montmorillonite (MMT) was completed. The characterization of modified montmorillonite (m-MMT) was performed via X-ray diffraction (XRD) and Thermogravimetric Analysis (TGA). In the second step, the synthesis of renewable polymeric nanocomposites from acrylated epoxidized soy bean oil (AESO), styrene (as a diluent) and modified montmorillonite (m-MMT) was achieved and the effect of increased nanofiller loading in mechanical and thermal properties of acrylated epoxidized soy bean oil (AESO) nanocomposites were analyzed by Dynamic Mechanical Analyzer (DMA), Differential Scanning Calorimeter (DSC) and Thermogravimetric Analysis (TGA). In the third step, the characterization studies of the acrylated epoxidized soy bean oil nanocomposites were completed by using X-ray diffraction (XRD), Atomic Force Microscopy (AFM) and Scanning Electron Microscopy (SEM) techniques. Desired exfoliated structure was achieved by using modified montmorillonite (m-MMT) in this kind of renewable polymeric nanocomposites. Resultant delaminated nanocomposites were found to have significant improvements both in thermal stability and dynamic mechanical performance as compared with virgin acrylated epoxidized soy bean oil based polymers even with one per cent of clay loading. Finally, biodegradability studies of the nanocomposites were done by using soil burial method and it was found that all resultant nanocomposites were biodegradable in soil and it was found that increasing the clay content increase the biodegradability of the nanocomposites. In order to confirm biodegradability studies, Lysogeny broth medium was used, and it was found that resultant nanocomposites were not antibacterial and bacteria species could easily promote their growth on these nanocomposites.
Keywords: Soy oil.; Polymeric composites.; Nanostructured materials.